An Emotion-aware Interactive Concert System: A Case Study in Realtime Physiological Sensor Analysis. Issue 3 (3rd July 2017) - van 't Klooster, Adinda; Collins, Nick
Abstract: An artistic concert system called BioCombat devised by the co-authors puts two performers' physiological states head to head, making their attempt to feel particular emotions the object of a live competition. Each performer provides sonic materials for each of eight emotional states; generative visuals are projected in concert, reactive to audio and physiological features, alongside an emotional scoring system also visible to the audience. This article describes the physiological sensing and emotion classification machinery required to support such a challenging real-time task, with both quantitative and qualitative evaluation results. The system draws upon recent research in the field. The designers offer solutions to the problems, and discuss the potential, of such current generation technology for artists.